Enrichment learning method in STEP-food technology at SMAK Santo Hendrikus Surabaya - Laurensia Maria Yulian Dwiputranti Darmoatmodjo; Victor Christian Kaharso; Netty Kusumawati; Virly Virly; Ninik Admawigati (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
The Student and Teacher Empowerment Program of Food Technology (STEP TP) is one of the flagship intracurricular programs at SMAK Santo Hendrikus Surabaya. However, the teachers who assist the STEP TP do not have any background in food technology, thus limiting their ability to provide comprehensive food technology learning materials to the students. This community service aims to assist the teachers in creating STEP TP learning materials in the form of teaching modules and videos, conduct a guest lecture, and hold a food processing workshop guided by food technology lecturers. The methodologies included conducting a focus group discussion with the school’s principal and teacher, surveying students’ interests and school facilities providing guest lectures and workshops, designing learning instruments, and evaluating the activities. The survey showed that most students were enthusiastic to learn about bread and cake processing, followed by beverage processing. In addition, the guest lecturer on the subject of food packaging was delivered to supplement the teachers' and students' knowledge other than food processing technology. Furthermore, students and teachers were taught to make pumpkin flour, which is applicable to bread and cake. Overall, the community service was fully supported by the partner's contribution. Modules and video had accepted by the school’s partner.